An Exclusively Skewed Distribution of Pediatric Immune Reconstitution Inflammatory Syndrome Toward the Female Sex Is Associated With Advanced Acquired Immune Deficiency Syndrome - de Souza Campos Fernandes, Regina Célia; Louvain de Souza, Thaís; da Silva Barcellos, Thiago; Medina-Acosta, Enrique (Frontiers in Pediatrics, 2019)
In human immunodeficiency virus and acquired immune deficiency syndrome (HIV/AIDS) patients with very low CD4 cell counts, there is a temporal relationship between administration of antiretroviral therapy (ART) and an increased inflammatory response state known as the immune reconstitution inflammatory syndrome (IRIS). The predominant clinical presentation of IRIS is an infectious disease that can be life-threatening. IRIS-related infectious events are distributed similarly between adult males and females, albeit a few studies have shown a skewing towards the male sex in pediatric IRIS. Here, we assessed sex-specific differences in the causes and extent of IRIS infectious events in HIV-infected pediatric patients on ART. We carried out a prospective clinical analysis (from 2000 to 2018) of IRIS-related infectious events after ART in a cohort of 82 Brazilian children and adolescents infected with HIV-1 through mother-to-child transmission as well as a comprehensive cross-referencing with public records on IRIS-related infectious causes in pediatric HIV/AIDS. Twelve events fulfilling the criteria of IRIS occurred exclusively in eleven females in our cohort. The median age at IRIS events was 3.6 years. The infectious causes included Mycobacterium bovis, varicella-zoster virus, molluscum contagiosum virus, human papillomavirus, cytomegalovirus, and Mycobacterium tuberculosis. In one female, there was regional bacillus Calmette-Guérin dissemination and cytomegalovirus esophagitis. There was complete health recovery after ten IRIS events without the use of corticosteroids or ART interruption. One case of IRIS-associated miliary tuberculosis was fatal. The biological female sex was a significant risk factor for IRIS events (odds ratio: 23.67; 95% confidence interval 95%: 1.341 – 417.7; P = 0.0016). We observed an effect of the advanced HIV/AIDS variable in IRIS females as compared with non-IRIS females (mean CD4+ T cell percentage 13.36% versus 18.63%; P = 0.0489), underpinning the exclusively skewed distribution towards the female sex of this cohort. Moreover, the IRIS females in our cohort had higher mean CD4+ T cell percentages before (13.36%) and after IRIS (26.56%) than those of the IRIS females (before IRIS, 4.978%; after IRIS, 13.81%) in previous studies conducted worldwide. We concluded that the exclusively skewed distribution of pediatric IRIS towards the female sex is associated with more advanced AIDS.